See how it's made. (New York : DK Pub., 2007)
Presents a comprehensive tour that follows the manufacture of a variety of everyday items from start to finish.
Includes index.
5.5
3-6
Keywords: Technology -- Miscellanea -- Juvenile literature; Technology; Technology